Accuracy of Transcerebellar Diameter in Detection of Gastational Agein Third Trimester in Cases of Intra Utrine Growth Restriction - Abo Elwan El-Sayed, Youssef; El Sayed Mohamed, Mohamed; Abdallah Abdel Salamand, Walid; Ramadan Ibrahim Soliman, Rana (International Journal of Psychosocial Rehabilitation, 2021)
The transverse cerebellar diameter (TCD) serves as a valid indicator of GA in the fetus and is a standard against which aberrations in other fetal parameters may be compared. The main goal of this research was to evaluate accuracy of transcerebellar diameter (TCD) in detection of gestational age in pregnancies with intrauterine growth restriction IUGR.   A case-Control study was carried out in department of Obstetrics and Gynecology at Zagazig University Hospital from June 2019 to Mars 2020. Included 52 women with normally progressing pregnancies during the third trimesters, 26 patients of them were normal pregnancies and 26 patients complains from IUGR in 3rd trimester at gestational age (27week to 37 week). Transabdominal ultrasound was performed on all patients, Fetal TCD was measured using the widest diameter of the cerebellum, measurement of fetal Bi-Parietal Diameter (BPD), Abdominal Circumference (AC), and Femur Length (FL).   There were positive correlation between GA by Last Menstrual Period (LMP) and sonar parameters at normal group in all parameters but highest was TCD with P value 0.000, but at IUGR group only TCD, AC and FL were significantly positive correlated with GA; and TCD were highly significant, both HC and BPD were irrelevant